GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 27527 species occurrences available in GBIF matching the query: TaxonKey: Evernia prunastri (L.) Ach.. The dataset includes 27527 records from 188 constituent datasets: 4 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 8 records from Jordal. 68 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 49 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 117 records from SANT-Lich. 12 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 2823 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 61 records from Naturalis Biodiversity Center (NL) - Botany. 29 records from PlutoF platform observations. 16 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 2 records from UFP - Herbário UFP - Geraldo Mariz. 1 records from BTCV Scotland - BTCV wildlife counts recording workshops. 9 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 117 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 1 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 28 records from BioFokus. 2 records from CESJ - Herbário Leopoldo Krieger. 2 records from Lichen.ie Data. 3434 records from Artdata. 14 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 1 records from MBM - Herbário do Museu Botânico Municipal. 11 records from OHN. 2 records from Données ONF Faune-Flore-Fonge. 1329 records from British Lichen Society - BLS Lichen Database: English churchyards. 11 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 39 records from Australia's Virtual Herbarium. 1 records from Herbier de Strasbourg. 8 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 105 records from iNaturalist research-grade observations. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from National System of Protected Areas in Poland - Fungi. 10 records from Universidad de Málaga: MGC-Lichen. 1 records from Louisiana State University Herbarium - Vascular Plants. 22 records from Estonian Museum of Natural History. 1 records from NINA botanical collection. 2 records from NMNH occurrence DwC-A. 1 records from Seewasen. 1 records from Küstenschutzwald. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Grillhütte Wettsaasen, Wiese, Hecken. 14 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 147 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 1 records from FFH-Gebiet "Calwer Heckengäu". 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from Pflanzen und Tiere im Burgwald. 1 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 1 records from Ireland's BioBlitz 2012. 167 records from naturgucker. 16 records from Institut Botanic de Barcelona, BC-Lichenotheca. 10 records from Erik Acharius lichen collection. 21 records from Cambridgeshire & Peterborough Biological Records Centre - Cambridge Lichen group data held by CPBRC.. 6 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 4 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Schatzinsel Norderney. 1 records from BB-Biodiversität a. 1 records from MfN - Fossil plants (Cenophytic). 231 records from Dutch Vegetation Database (LVD). 8 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 1 records from Rådgivende Biologer. 73 records from Lichen herbarium, Trondheim (TRH). 457 records from Lichen herbarium, Oslo (O). 81 records from IBF Monitoring of Lichens. 30 records from The Lichen Collection at the Botanische Staatssammlung München. 21 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 29 records from Natural History Museum (London) Collection Specimens. 9 records from Ireland's BioBlitz. 28 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 7 records from Ibaraki Nature Museum,Lichen collection. 380 records from Herbarium Senckenbergianum (FR) - Fungi. 6 records from Australian National Herbarium (CANB). 2 records from Australian Antarctic Division Herbarium. 16 records from Canadian Museum of Nature Herbarium. 16 records from CABI Bioscience Fungus Collection. 2227 records from British Lichen Society - BLS Lichen Database: Scotland. 148 records from Real Jardin Botanico, Madrid: MA-Lichen. 87 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 124 records from Michigan State University Herbarium Lichens. 3 records from Lichen Collection of National Museum of Nature and Science. 342 records from Arizona State University Lichen Collection. 15 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 118 records from Danish Mycological Society, fungal records database. 18 records from California State University, Chico. 7 records from Herbarium Berolinense. 234 records from Lichen Herbarium Berlin. 569 records from Biologiezentrum Linz. 143 records from Banc de dades de biodiversitat de Catalunya-LiqueCat. 7 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 7 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 3 records from USU-UTC Specimen Database. 61 records from Lichen collection. 96 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 177 records from Harvard University Herbaria. 1 records from Staffordshire Ecological Record - SER Site-based Surveys. 164 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 179 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from BÜG. 1 records from LaBoOb02. 1 records from Danielsberg (Mölltal, Kärnten). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Gemeinde Sursee. 1 records from Schlern - (Bozen). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Neckartalsüdhang (Horb). 1 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1 records from Philosophenwald und Wieseckaue in Gießen. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Unser Schulgelände. 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Gurgltal (Tarrenz). 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Stadtpark Sulzbach-Rosenberg. 1 records from Schlattstaller Tal (Lenningen). 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 147 records from Lichens of North-Eastern Poland. 68 records from Natural History Museum, University of Tartu. 79 records from Lichens of Biebrza National Park. 133 records from Herbarium of Umeå University (UME). 3720 records from British Lichen Society - BLS Lichen Database: England. 5 records from R. L. McGregor Herbarium Lichen Collection. 2 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 413 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from Artenvielfalt am Schlern. 19 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Tag der Artenvielfalt im Taubental. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Lich. 10 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 17 records from Bryophyte Collection - University of Washington Herbarium (WTU). 133 records from Lichen Collection - University of Washington Herbarium (WTU). 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 2913 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 1 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Lichens. 1 records from Fungi collection of the Botanical Museum of the University of Oulu. 1007 records from British Lichen Society - BLS Lichen Database: Wales. 5 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Faun. 5 records from ArtenFinder. 236 records from Lund Botanical Museum (LD). 2 records from National Trust - Ickworth species data held by The National Trust.. 45 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 2 records from Irish Records from the Fungal Records Database of Britain and Ireland. 21 records from Fieldjournal.org observation database. 14 records from Field Museum of Natural History (Botany) Lichen Collection. 241 records from Norwegian Species Observation Service. 6 records from Herbarium BSG Lichenes. 6 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from Herbier Louis-Marie (QFA) - Collection de lichens. 127 records from Lichens of Knyszyn Forest. 7 records from Staffordshire Ecological Record - SER Species-based Surveys. 7 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from All observations extracted from the Flora of Northumberland and Durham 1831. 629 records from Botany (UPS). 40 records from Seil Natural History Group - SNHG Biological Records Dataset. 3 records from Estonian Nature Observations Database. 1 records from Lichen herbarium, NMBU. 62 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 4 records from R - Herbário do Museu Nacional. 3 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 11 records from Herbarium WRSL, Lichens Collection. 2 records from Lichen specimen database of Faurie collection. 1 records from Lichen collection, Norwegian Forest and Landscape Institute. 2 records from Données ONF Faune-Flore-FOnge. 698 records from Lichen field notes, Oslo (O). 10 records from Ecofact. 87 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 2 records from Allan Herbarium (CHR). 83 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 12 records from Hertfordshire Biological Records Centre - Hertfordshire Lichen Orchard Survey 2011. 11 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 320 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 43 records from Tromsø Museum, Lichens. 3 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 11 records from Geneva Herbarium – General Collection (G). 3 records from Northern Ireland Environment Agency - EHS Species Datasets. 39 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 141 records from Lichen herbarium, UiB. 2 records from Herbarium specimens of Limoges university (LIMO). 954 records from Fungi (S). 39 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences